No benefit of more intense follow-up after surgery for colorectal cancer in the risk group with elevated CEA levels – An analysis within the COLOFOL randomized clinical trial. Issue 8 (August 2021) - Egenvall, Monika; Martling, Anna; Veres, Katalin; Horváth-Puhó, Erzsébet; Wille-Jørgensen, Peer; Høirup Petersen, Sune; Laurberg, Søren; Sørensen, Henrik Toft; Syk, Ingvar; ,; Andersen, Per Vadgaard; Christensen, Henrik; et al.
Abstract: Background: Patients with colorectal cancer were examined to determine (1) whether elevated carcinoembryonic antigen (CEA) levels, either before treatment or after surgery, was associated with an increased risk of overall or colorectal cancer-specific mortality or recurrence, and (2) whether high intensity follow-up would benefit those patients. Materials and methods: Post-hoc analysis based on 2509 patients that underwent surgery for colorectal cancer, stage II or III, in the COLOFOL randomized trial with 5-year follow-up. Serum CEA levels were ascertained before treatment and one month after surgery. Follow-up examinations included computed tomography of the thorax and abdomen and serum CEA sampling. Patients were randomized to examinations at either 6, 12, 18, 24, and 36 months (high-intensity group) or at 12 and 36 months after surgery (low-intensity group). Levels of CEA >5 μg/l were defined as elevated. Results: Elevated CEA levels before treatment were associated with increased risk of recurrence (hazard ratio [HR], 1.49; 95% confidence interval [CI]: 1.22–1.83), colorectal cancer-specific mortality (HR, 1.44; 95% CI: 1.08–1.91), and overall mortality (HR, 1.38; 95% CI: 1.07–1.78). Elevated CEA levels after surgery were associated with increased colorectal cancer-specific mortality (HR, 1.68; 95% CI: 1.08–2.61) and overall mortality (HR, 1.79; 95% CI: 1.22–2.63). The intensity of the follow-up regimen had no effect on 5-year outcomes in patients with elevated CEA levels. Conclusion: Both pre-treatment and post-surgery elevated serum CEA levels were associated with increased overall and cancer-specific mortality. Intensified follow-up showed no benefit over low-intensity follow-up in this high-risk group of patients with elevated CEA levels.